Out-of-Pocket Costs of Complementary Medicine Following Cancer and the Financial Impact in a Setting With Universal Health Coverage: Findings From a Prospective Cohort Study. Issue 10 (October 2021) - Bhoo-Pathy, Nirmala; Subramaniam, Shridevi; Khalil, Sadia; Kimman, Merel; Kong, Yek-Ching; Ng, Chiu-Wan; Bustamam, Ros Suzanna; Yip, Cheng-Har
Abstract : PURPOSE: To determine household spending patterns on complementary medicine following cancer and the financial impact in a setting with universal health coverage. METHODS: Country-specific data from a multinational prospective cohort study, Association of Southeast Asian Nations Costs in Oncology Study, comprising 1, 249 cancer survivors were included. Household costs of complementary medicine (healthcare practices or products that are not considered as part of conventional medicine) throughout the first year after cancer diagnosis were measured using cost diaries. Study outcomes comprised (1) shares of household expenditures on complementary medicine from total out-of-pocket costs and health costs that were respectively incurred in relation to cancer, (2) incidence of financial catastrophe (out-of-pocket costs related to cancer ≥ 30% of annual household income), and (3) economic hardship (inability to pay for essential household items or services). RESULTS: One third of patients reported out-of-pocket household expenditures on complementary medicine in the immediate year after cancer diagnosis, accounting to 20% of the total out-of-pocket costs and 35% of the health costs. Risk of financial catastrophe was higher in households reporting out-of-pocket expenditures on complementary medicine (adjusted odds ratio: 1.39 [95% CI, 1.05 to 1.86]). Corresponding odds ratio within patients from low-income households showed that they were substantially more vulnerable: 2.28 (95% CI, 1.41 to 3.68). Expenditures on complementary medicine were, however, not associated with economic hardship in the immediate year after cancer diagnosis. CONCLUSION: In settings with universal health coverage, integration of subsidized evidence-based complementary medicine into mainstream cancer care may alleviate catastrophic expenditures. However, this must go hand in hand with interventions to reduce the use of nonevidence-based complementary therapies following cancer.